Android-based mobile application for Felda United Football Club (FUFChamp) - Nurul Khalidah, Raduan (2019)
Currently, almost all Malaysian have an interest in football. There is a lot of mobile application for football, but most of it gives information about all football teams. FELDA United Football Club (FUFC) is one of the famous football team in Malaysia. FUFC itself has its own website for an update about the teams. The problem is, the admin rarely posts any update on the websites. Most of the time, the admin will update it on FUFC social media such as Twitter, Facebook, and Instagram. If the game is promoted properly in Malaysia, the fans and supporters will be increasing. To develop the interest in this sport, a platform which functions as a mediator between the fans and the sports events is needed. The need of the user to know about the results of the football tournament is fulfilled by the mobile application. Moreover, the system enables users to know the latest news about FELDA United football team. This feature helps users to get to know more about the team. Besides, it is also a medium for knowing the basic information about the players for this team. This Android application is a bridge for the users in the football world, especially for the FUFC fans. This project uses the Rapid Application Development (RAD) model to implement the development process. For the project development, Java language, Extensible Markup Language (XML), Hypertext Mark-up Language (HTML), Cascading Style Sheets (CSS) language and Hypertext Preprocessor (PHP) language being used as the development language and MYSQL as a database for the admin. FUFChamp is a mobile application that has features such as latest news, scoreboard, player’s information, highlight videos, and images gallery. This application is suitable for users of any age.